ANTIOXIDANT ACTIVITY OF CASHEW APPLE DREG EXTRACT AND THEIR EFFECT IN TRADITIONAL PROCESSING OF COCONUT OIL - Yunita Arian Sani Anwar (UNIVERSITAS SEBELAS MARET (UNS), 2017)
The aim of this study was to determine antioxidant activity of cashew apple dreg extract and their antioxidant activity in traditional processing of coconut oil. Cashew apple dreg was extracted by ethanol and fractionation by DCM, n-hexane and water. The antioxidant activity from dreg extract was determined using 2,2-diphenyl-1-pycrylhydrazil (DPPH). The result showed that all ethanol fractions of cashew apple dreg contain flavonoid and tannins/polyphenols. Based on scavenging DPPH all of ethanol fractions showed antioxidant activity. The greatest DPPH inhibition was observed for ethanol extract. On the contrary, n-hexane fraction showed the lowest IC50. Application in traditional processing of coconut oil showed that the addition 2,5% ethanol extract provide the best product according to the lower content of peroxide value and TBA number.